Estudio de prefactibilidad de una empresa productora de hidróxido de litio a base de carbonato de litio - Atencio Ravello, Edgar Bryan (2021)
This investment project will show the pre-feasibility study for the production of lithium hydroxide from lithium carbonate. Currently, the global consumption of lithium hydroxide is in continuous growth, proof of this are the statements of HSBC "The price of lithium will increase by 150% by 2020" (Source: The Investor). Mainly, due to the increase in sales of electric cars that have lithium batteries. For this reason, the project focuses on transforming lithium carbonate into lithium hydroxide in order to meet the existing unmet demand for raw material for the production of lithium-based batteries. In the first place, in chapter 1 we addressed the research problem which we seek to solve by increasing the global supply of lithium hydroxide, in addition, the general and specific objectives were established, the technical, economic and social justifications were made public. It should be noted that the working hypothesis, the referential and conceptual framework were determined. Secondly, chapter 2 carried out the market study in which the product, geographic area, project demand, competitive and commercial strategy were defined. Likewise, an analysis of the demand and supply was carried out and the inputs, substitutes and complementary goods of our product were recognized. Third, in Chapter 3 we discussed and analyzed the results of our research in order to be able to confirm or deny the viability of this project.